SERTIFIKASI MINYAK SAWIT INDONESIA DALAM MEWUJUDKAN BISNIS GLOBAL BERKELANJUTAN - Ayu Herlin Norma Yunita; Yusuf Adiwibowo; Nuzulia Kumala Sari (Jurnal Magister Hukum Perspektif, 2026)
The implementation of the European Union Deforestation Regulation (EUDR) has had a significant impact on Indonesia’s palm oil exports to the European Union market. This policy mandates compliance with sustainability and traceability standards, as well as guarantees that traded products no longer originate from deforestation practices. This poses legal and economic challenges for businesses. This study examines how the Indonesian Sustainable Palm Oil (ISPO) certification legal framework promotes sustainable palm oil business practices in Indonesia, as well as the differences in standards between ISPO and the EUDR that could Email potentially lead to legal consequences regarding legal certainty for Indonesian palm oil businesses in the global market. This study employs a normative legal approach with a comparative analysis of national and international regulations. The findings indicate that the ISPO legal framework under Presidential Regulation No. 16 of 2025 which includes seven sustainability principles remains stagnant at 31% coverage due to high costs and a lack of incentives. There are substantial gaps between ISPO and the EUDR in four key areas: definitions of forest and deforestation, geolocation data requirements, deforestation time limits, and the protection of indigenous peoples’ rights through the Free, Prior, and Informed Consent (FPIC) mechanism. This gap creates legal uncertainty for businesses and threatens approximately US$3.2 billion in annual exports to the European Union market. This study recommends the need to harmonize legal definitions in line with international standards, particularly those of the FAO and the EUDR, the integration of a geolocation-based traceability system, the strengthening of protection for the FPIC principle within ISPO regulations, the provision of support and incentives for smallholders to meet sustainability standards, and the strengthening of Indonesia’s economic diplomacy to expand international acceptance and recognition of ISPO certification as an instrument for sustainable palm oil governance.   Keywords: Indonesian Sustainable Palm Oil (ISPO), European Union Deforestation Regulation (EUDR), Sustainable Business, Legal Certainty, Global Market Access